Advances in Computer Science and Information Engineering Volume 1 - Jin, David; Lin, Sally; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
CSIE2012 is an integrated conference concentrating its focus on Computer Science and Information Engineering . In the proceeding, you can learn much more knowledge about Computer Science and Information Engineering of researchers from all around the world. The main role of the proceeding is to be used as an exchange pillar for researchers who are working in the mentioned fields. In order to meet the high quality of Springer, AISC series, the organization committee has made their efforts to do the following things. Firstly, poor quality paper has been refused after reviewing course by anonymous referee experts. Secondly, periodically review meetings have been held around the reviewers about five times for exchanging reviewing suggestions. Finally, the conference organizers had several preliminary sessions before the conference. Through efforts of different people and departments, the conference will be successful and fruitful.
From the Contents: Design on Architecture of Internet of Things -- XML-Based Structural Representing Method for Information of Things in Internet of Things -- A QoS-Aware Web Service Orchestration Engine Based on Actors -- Emergency Management Application Based on Spatial Information Cloud Service -- Research on Complex Networks Evolution Model -- Using ASP.NET to Develop Intelligent Online Ordering System in E-commerce -- Passive Energy-Dissipation Control for Aqueduct Structural under Earthquake Based on SIMULINK -- Research on Psychological Characteristics of Undergraduates and Construction of Study Style for Electronic-Information-Type Specialties -- Research on Self-Organization Mechanism of Discipline Cluster System.
Keywords: Engineering; Engineering mathematics; Engineering; Computational Intelligence; Computer Engineering; Appl.Mathematics/Computational Methods of Engineering